Toward 3D Bioprinting of Osseous Tissue of Predefined Shape Using Single‐Matrix Cell‐Bioink Constructs. Issue 9 (20th January 2023) - Gu, Yawei; Pigeot, Sebastien; Ahrens, Lucas; Tribukait‐Riemenschneider, Fabian; Sarem, Melika; Wolf, Francine; García‐García, Andres; Barbero, Andrea; Martin, Ivan; Shastri, V. Prasad
Abstract: Engineering living bone tissue of defined shape on‐demand has remained a challenge. 3D bioprinting (3DBP), a biofabrication process capable of yielding cell constructs of defined shape, when combined with developmental engineering can provide a possible path forward. Through the development of a bioink possessing appropriate rheological properties to carry a high cell load and concurrently yield physically stable structures, printing of stable, cell‐laden, single‐matrix constructs of anatomical shapes is realized without the need for fugitive or support phases. Using this bioink system, constructs of hypertrophic cartilage of predesigned geometry are engineered in vitro by printing human mesenchymal stromal cells at a high density to drive spontaneous condensation and implanted in nude mice to evoke endochondral ossification. The implanted constructs retain their prescribed shape over a 12‐week period and undergo remodeling to yield ossicles of the designed shape with neovascularization. Microcomputed tomography, histological, and immunohistochemistry assessments confirm bone tissue characteristics and the presence of human cells. These results demonstrate the potential of 3DBP to fabricate complex bone tissue for clinical application. Abstract : 3D bioprinting of hard tissues requires systems that can withstand handling and survive in vivo implantation without undergoing significant deformation. Herein, the implementation of a workflow for the engineering osseous tissue of predefined shape through the in vivo remodeling of a hypertrophic cartilage template based on bioinks that possess appropriate rheology to yield physically robust and anatomically accurate structures is presented.